2019
DOI: 10.1056/nejmoa1808312
|View full text |Cite
|
Sign up to set email alerts
|

Partial Oral versus Intravenous Antibiotic Treatment of Endocarditis

Abstract: Background Patients with infective endocarditis on the left side of the heart are typically treated with intravenous antibiotic agents for up to 6 weeks. Whether a shift from intravenous to oral antibiotics once the patient is in stable condition would result in efficacy and safety similar to those with continued intravenous treatment is unknown. Methods In a randomized, noninferiority, multicenter trial, we assigned 400 adults in stable condition who had endocarditis on the left side of the heart caused by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
348
1
17

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 580 publications
(421 citation statements)
references
References 29 publications
12
348
1
17
Order By: Relevance
“…4). It is important to note that our 4% non-inferiority margin is already much smaller than the noninferiority margins used in recent trials of antibiotic treatment duration in patients with serious bacterial infections [12][13][14][15], and is also much lower than the US Federal Drug Administration recommendation of noninferiority margins for ventilator-associated pneumonia [16]. Therefore, we have opted to maintain our current overall sample size target (n = 3626) for the BALANCE main trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). It is important to note that our 4% non-inferiority margin is already much smaller than the noninferiority margins used in recent trials of antibiotic treatment duration in patients with serious bacterial infections [12][13][14][15], and is also much lower than the US Federal Drug Administration recommendation of noninferiority margins for ventilator-associated pneumonia [16]. Therefore, we have opted to maintain our current overall sample size target (n = 3626) for the BALANCE main trial.…”
Section: Discussionmentioning
confidence: 99%
“…The BALANCE-Ward pilot RCT patients had an overall 90-day mortality rate of 17/133 (12.8%, 95% CI 8.1-19.5%), which was similar to the 90-day mortality rate in the ICU pilot RCT (17/115, 14.8%, 95% CI 9.4-22.4%) (p = 0.65; Table 3) and mortality estimates from the main BALANCE RCT as of 600 patients enrolled (104/600, 17.3%, 95% CI 14.5-20.6%). The patients in the BALANCE-Ward pilot had a shorter median (IQR) length of hospital stay (6 (4-12) vs 20(12-43) days, p < 0.001) and more antibiotic-free days by day 28 (14(14-21) vs 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), p < 0.0001) ( Table 3). Only one patient was lost to follow-up at 90 days, but there are ongoing efforts to ascertain final vital status for this patient.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…There are, fortunately, also biofilm infections where antibiotic prophylactics and treatment are not so difficult e.g. endocarditis and successful antibiotic treatment can be obtained, even with orally administered antibiotics in stabilized patients after an initial intravenous course of appropriate antibiotic drugs .…”
Section: Special Situation Biofilm Infectionsmentioning
confidence: 99%
“…This is especially the case with orally administered β‐lactams whose bioavailability and doses are much lower than their IV counterparts . However, studies showed that PO antibiotics are as effective as IV antibiotics for other difficult to treat infections including left‐sided endocarditis and bone‐joint infections …”
mentioning
confidence: 99%